A simple synthesis and thermal decomposition kinetics of MnHPO 4•H2O rod-like microparticles obtained by spontaneous precipitation route - Boonchom, Banjong; Danvirutai, Chanaiporn (My University, 2008)
Manganese hydrogenphosphate monohydrate (MnHPO4•H 2O) was prepared by a rapid precipitation (10 min) using Mn(c)-H 3PO4 system at ambient temperature. The thermal treatment of MnHPO4•H2O at 773 K found to be a manganese pyrophosphate (Mn2P2O7). The activation energies of the major mass loss step were calculated by Ozawa and Kissinger-Akahira-Sunose (KAS) isoconversional methods, which were used to determine the decomposition mechanism. The energy absorptions at the vibrational level of thermal decomposition steps were calculated and were compared with spectroscopic data, which were used to identify the molecules or ions that were released in each thermal transformation steps. The synthesized MnHPO 4•H2O and its thermal decomposition product Mn 2P2O7 were investigated by scanning electron microscope (SEM), X-ray powder diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The SEM micrographs show rod-like microparticles for the synthesized MnHPO4•H2O and porosity on surface of the decomposition product Mn2P2O7, which are important for specific applications.
Keywords: Manganese hydrogenphosphate monohydrate; Non-isothermal kinetics; Porosity nanoparticles; Rod-like microparticles